Development of Moral Judgment according to Kohlberg as an Academic Performance Determining Factor in Social Sciences for a Group of Secondary Education Students - José Díaz-Serrano (Revista Electrónica Educare)
This study aims at defining the relation between the students’ moral development level and their academic performance in the subject of Social Sciences-Geography, with the participation of twelve students enrolled in the third year of compulsory secondary education in school of Murcia, Spain. Kohlberg theorized the moral judgment development process in which people go through six stages, identifying in each one of them how we react when confronted with a moral dilemma; an instrument designed for this study, based on such theory, will allow us to know the stage of moral development of the participants. The results will reveal a tendency to a direct and positive relation, leading to the conclusion that it is interesting to examine the stage of moral judgment in the classroom. In addition, some educational and research recommendations are provided at the end of this paper.